Infected ascites: Distinguishing secondary peritonitis from spontaneous bacterial peritonitis in a cirrhotic patient with classic symptoms. (2017) - Lu, Marvin Louis Roy; Agarwal, Akanksha; Sloan, Josh; Kosmin, Aaron
Abstract: Introduction: Spontaneous bacterial peritonitis can be differentiated from secondary bacterial peritonitis by the absence of a surgically treatable intra-abdominal source of infection. However, oftentimes this is unapparent and other clinical clues need to be sought after to make the right diagnosis. Case: A 64-year-old woman was admitted because of three days of worsening diffuse abdominal pain and distention. She was morbidly obese and had a history of non-alcoholic steatohepatitis (NASH) cirrhosis. She was febrile at 38.2 °C. Her abdomen was soft, diffusely tender and distended with a reducible umbilical hernia. Laboratory exam showed a white blood cell count 6700/mcl. Ascitic fluid analysis showed a yellow cloudy fluid with an absolute neutrophil count (ANC) of 720 cells/m 3, a total protein of 1.1 g/dl and a lactate dehydrogenase of 242 IUł. She was given ceftriaxone and albumin. The ascitic fluid culture grew pansensitive Viridans streptococcus. The following days she continued to have fever and abdominal pain and a repeat paracentesis was done which showed improvement in her ANC. Abdominal computed tomography scan was done which showed hernia inflammation with a rim-enhancing fluid collection. Surgery was consulted who did a primary repair of the umbilical hernia and over the next few days the patient improved and was discharged stable. Conclusion: Persistence of signs and symptoms of peritonitis despite improvement in ascitic fluid analysis in cirrhotic patients treated for or early relapse of peritonitis with the same organism should prompt the physician to evaluate for secondary peritonitis and surgical management should be considered for potentially correctable sources.